Strongholds of the Ribeira Sacra in the Area Surrounding the Monastery of Santo Estevo de Ribas de Sil - Valdés Blanco-Rajoy, Rosario (Madrygal. Revista de Estudios Gallegos, 2020)
The main purpose of the paper is a case study of a geographical area of the left bank of the River Sil at the confluence with the River Miño that allows us to approach the phenomenon of landscape fortification during the Middle Ages. Contrasting written sources with archaeological records, we address some issues in relation to the morphological development of fortified settlements, the role played in the management of the territory, and also how contemporary and nearby strongholds probably interacted.